Reseña de: Rio, Alice, Legal Practice and the Written World in the Early Middle Ages. Frankish Formulae, c.500-1000 - Bañón Pardo, Alejandro (Espacio Tiempo y Forma. Serie III, Historia Medieval, 2019)
Rio, Alice, Legal Practice and the Written World in the Early Middle Ages. Frankish Formulae, c.500-1000. Nueva York. Cambridge University Press, 2009. xii + 299 pp. ISBN-13: 978-0-511-53684-7